SECULARISM IN INDIA MYTH OR REALITY: AN EXPLANATORY STUDY - Aqib Yousuf Rather (RADJA PUBLIKA, 2022)
An impetus was given to the discussion on whether or not Indian secularism is a myth or a reality. A secular society is one in which individuals are free to practise their religion of choice. The Constitution of India recognises and upholds the principle of religious toleration, making India a nation that is home to a number of distinct faiths. The term